2023
DOI: 10.3389/fphar.2023.1145188
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate inhibits airway remodeling in asthma via the MAPK signaling pathway

Abstract: Background: Artesunate (ART), is a semi-synthetic water-soluble artemisinin derivative extracted from the plant Artemisia annua, which is often used to treating malaria. In vivo and in vitro studies suggested it may help decrease inflammation and attenuate airway remodeling in asthma. However, its underlying mechanism of action is not elucidated yet. Herein, an attempt is made to investigate the ART molecular mechanism in treating asthma.Methods: The BALB/c female mice sensitized via ovalbumin (OVA) have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…HE staining was used to evaluate the airway inflammation. The inflammation surrounding the bronchus and blood vessels was observed using an optical microscope in each section, with the inflammation score ranging from 0 to 5 points ( Zhang et al, 2023 ). PAS staining was used to assess airway mucus secretion, while masson’s trichrome staining evaluated collagen deposition.…”
Section: Methodsmentioning
confidence: 99%
“…HE staining was used to evaluate the airway inflammation. The inflammation surrounding the bronchus and blood vessels was observed using an optical microscope in each section, with the inflammation score ranging from 0 to 5 points ( Zhang et al, 2023 ). PAS staining was used to assess airway mucus secretion, while masson’s trichrome staining evaluated collagen deposition.…”
Section: Methodsmentioning
confidence: 99%
“…(4) Patients who are allergic to the active ingredient of the vaccine or to any dressing. (5) Patients who are combined with other respiratory diseases, such as allergic bronchopulmonary aspergillosis, hypersensitivity pneumonia, pulmonary malignancy, pulmonary, bronchiectasis, tuberculosis, idiopathic pulmonary interstitial fbrosis, and pulmonary sarcoidosis. In addition, inhalation technique and compliance were checked.…”
Section: Study Populationmentioning
confidence: 99%
“…Studies showed that omalizumab responders had signifcantly younger age in the adult subgroup, higher pretreatment total serum IgE level, percent predicted FEV1, and fractional exhaled nitric oxide (FeNO) than nonresponders [4]. Other studies indicated responsiveness of omalizumab is not associated with pretreatment clinical biomarkers, including FeNO, serum total IgE, FEV1, and blood eosinophils [5]. So far there is no consensus opinion.…”
Section: Introductionmentioning
confidence: 99%
“…Galangin [64] OVA-induced asthma in mice TGF-β1, MMP9, VEGF Artesunate [65] OVA-induced asthma in mice MAPK Ginkgolic acid [66] Pulmonary fbrosis in mice Smad4 caused by oxidative stress [75,76]. Moreover, naringenin was shown to have a signifcant therapeutic on Mycoplasma pneumoniae-induced lung injury in mice by inhibiting pulmonary fbrosis and inhibiting the secretion of infammatory cytokines such as IL-6, IL-1β, TNF-α, and TGF-β [60].…”
Section: Te Efect Of Specifc Herbal Compounds On Emtmentioning
confidence: 99%
“…Artesunate is a semisynthetic single compound isolated from the plant Artemisia annua. Artesunate may decrease infammation and attenuate airway remodeling in asthmatic mice via the MAPK signalling pathway [65].…”
Section: Te Efect Of Specifc Herbal Compounds On Emtmentioning
confidence: 99%